A comparative dosimetric study of hypofractionated radiotherapy with different target volume delineation approaches in breast cancer patients after implant-based reconstruction - Ding, Lipeng; Wang, Xu; Zheng, Zhangcai; Long, Jianping; Miao, Guoying; Yang, Tao; Li, Shuxia; Dong, Na; Gao, Liying (Frontiers in Oncology, 2026)
PurposeThis study dosimetrically compares hypofractionated VMAT plans using the updated ESTRO-ACROP guidelines versus conventional delineation in patients undergoing immediate implant-based breast reconstruction after mastectomy.MethodsWe retrospectively enrolled 22 patients with immediate implant-based reconstruction post-mastectomy (12 left-sided, 10 right-sided), treated between January 2022 and June 2025. All patients underwent CT simulation; those with left-sided cancer were positioned using deep inspiration breath-hold (DIBH), and those with right-sided cancer under free breathing. For each patient, conventional (C-TVD) and ESTRO-ACROP guideline-based (E-TVD) target volumes were independently delineated on the same CT dataset. Hypofractionated VMAT plans were designed using a 6-MV beam, single-isocenter, dual-arc technique, prescribing 40.05 Gy in 15 fractions to the planning target volume (PTV). All plans were normalized to ensure ≥95% PTV coverage by the prescribed dose. Dose-volume parameters for targets and organs at risk (OARs) were then compared between the two delineation approaches.ResultsThe conformity index (CI) of E-TVD was inferior to that of C-TVD; however, E-TVD achieved superior 95% prescription dose coverage of the target volume. Compared with C-TVD, E-TVD resulted in significantly lower V20 and Dmean to the ipsilateral lung, with differences reaching statistical significance (P < 0.05). For the heart, E-TVD was associated with significantly lower V20, as well as lower Dmax and Dmean to the left anterior descending coronary artery (LAD), with all differences reaching statistical significance (P < 0.05). Subgroup analyses stratified by left versus right breast cancer revealed that in left breast cancer patients, E-TVD resulted in statistically significant reductions in ipsilateral lung V20, V10, and Dmean; bilateral lung V20; heart V20; LAD Dmax and Dmean; and contralateral breast Dmean (all P < 0.05). In right breast cancer patients, E-TVD was associated with significantly lower ipsilateral lung Dmean and contralateral breast Dmean (both P < 0.05).ConclusionsIn patients with breast cancer who undergo total mastectomy followed by immediate implant-based breast reconstruction, the E-TVD approach confers superior protection to organs at risk.